Exploring the Lived Experiences of Self-Care among Patients with Type 2 Diabetes Mellitus in Indonesia: A Phenomenological Study - Aria Wahyuni; Wiwit Febrina; Fauziah Rahmah Dewi; Rola Oktorina (Faculty of Nursing, Universitas Hasanuddin, 2026)
Aims: This study aimed to explore the lived experiences of patients with type 2 Diabetes Mellitus (T2DM) in Indonesia regarding their self-care practices and the influence of psychosocial, cultural, and spiritual factors in managing the disease. Methods: A qualitative phenomenological study was conducted using in-depth interviews with 15 purposively selected patients with T2DM from primary healthcare centers in Bukittinggi, Indonesia. Eligible participants had a T2DM diagnosis, no severe cognitive or functional impairment, and provided informed consent. Data were collected between December 2024 and March 2025 using semi-structured interviews and analyzed using Colaizzi’s seven-step method, with NVivo 12 used only for data management. Results: Six themes emerged: acceptance and meaning-making in the following of diagnosis, physical activity in daily life, strategies for blood glucose monitoring, medication adherence and herbal use, dietary management and challenges, and diabetic foot care practices Conclusion: Self-care among T2DM patients is deeply influenced by emotional resilience, spiritual values, and family roles. Tailored and culturally appropriate interventions are essential for enhancing diabetes management and long-term self-care in community settings.